Kendala yang Dihadapi dalam Penerapan Dukcapil DiGi Mobile di Dinas Kependudukan dan Pencatatan Sipil Kota Pariaman - Imrahmi, Fadhiah; Alhadi, Zikri (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research discusses the obstacles faced in implementing Dukcapil DiGi Mobile in Dukcapil Pariaman City. Effectiveness is a measuring tool to determine whether or not a predetermined target has been achieved. There are many factors that can influence effectiveness, both internal and external constraints. The presence of Dukcapil DiGi Mobile as an online service for population and civil registration services in Pariaman City aims to make it easier for the public to manage population administration effectively and efficiently. However, in its implementation there are still several obstacles in implementing Dukcapil DiGi Mobile. This research aims to determine the obstacles faced in implementing population document services through the DiGi Mobile application using Hansen and Mowen's theory which groups various kinds of obstacles into internal and external obstacles. The results of this research show what obstacles are faced in implementing Dukcapil DiGi Mobile in Dukcapil Pariaman City.